Review of Factors Affecting Tax Compliance And Tax Ratio Target Achievement - Loso Judijanto (Nomico, 2024)
This article provides a comprehensive review of the factors influencing tax compliance and the achievement of targeted tax ratios, employing literature review and qualitative analysis approaches. The primary objective is to identify and analyze the determinants that affect taxpayers' compliance behavior and how these factors contribute to meeting the desired tax ratio targets set by governments. Tax compliance is crucial for ensuring sufficient public revenue, which supports economic development and public services. Achieving targeted tax ratios is essential for maintaining fiscal stability and promoting equitable economic growth. The study explores various factors, including economic, psychological, and institutional elements, that impact tax compliance. Economic factors such as income levels, tax rates, and perceived fairness of the tax system are examined alongside psychological factors such as taxpayer attitudes, trust in government, and perceived benefits of public spending. Institutional factors, including the efficiency of tax administration and the legal framework, are also considered. By synthesizing findings from existing literature, this article highlights the complex interplay of these factors and suggests strategies for policymakers to enhance tax compliance and achieve targeted tax ratios. The findings underscore the importance of a multifaceted approach that considers both taxpayer behavior and systemic reforms to improve tax systems' effectiveness.